Modelling the riskiness in country risk ratings - Hoti, Suhejla; McAleer, Michael (Emerald, 2005)
The importance of country risk is underscored by the existence of several prominent country risk rating agencies. These agencies combine information regarding alternative measures of economic, financial and political risk into associated composite risk ratings. As the accuracy of such country risk measures is open to question, it is necessary to analyse the agency rating systems to enable an evaluation of the importance and relevance of agency risk ratings. The book focuses on the rating system of the international country risk guide. Time series data permit a comparative assessment of risk ratings for 120 countries, and highlight the importance of economic, financial and political risk ratings as components of a composite risk rating. The book analyses various univariate and multivariate risk returns and corresponding symmetric and asymmetric models of conditional volatility, as well as conditional correlations.
Includes index.
Keywords: Country risk -- Mathematical models.; elektronické knihy; electronic books